Potential impact of sanitary and phytosanitary barriers on trade for the Americas - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
This report investigates the prospects countries in the Americas have in their efforts to meet the SPS mandates of the World Trade Organization (WTO), It identidies several trends that appear to be occurring as countries attempt to meet obligations under the WTO. An understandind of these trends is important considering that many ot the SPS policy issues have evolved relatively quickly and haphazardly over the past few years with little opportunity for analysis or reflection. Since these measures are continuing to evolve at a rapid pace, our policy recommendations consider the success of several short-term actions and then focus on the long-term needs and objectives based on today's environment. The issue of compliance with WTO obligations is important because it marks the first occasion where SPS has been brought formally into the dialogue concerning trade.